Malassezia Pachydermatis Fungemia: A Dog-Owner’s Dilemma - Syamasis Bandyopadhyay; Aheli Ghosh Dastidar; Sandip Kumar Chandra; Parineeta Singhal (Case Reports in Clinical Practice)
The present case report describes a unique instance of a 70-year-old male presenting with high-grade fever, severe respiratory distress, and drowsiness. He was diagnosed with Malassezia pachydermatis fungemia, attributed to his proximity to pet dogs. Treatment with empirical broad-spectrum antibiotics and echinocandin antifungal agents resulted in no improvement in the patient’s condition. Upon switching to fluconazole, the patient showed gradual improvement after three days and achieved complete resolution of the infection within two weeks. This report highlights a rare case of bloodstream infection caused by Malassezia pachydermatis and underscores the importance of thorough history-taking in diagnosing rare conditions.